1988
DOI: 10.1128/mcb.8.8.3338
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific gene expression in mouse hepatocytes cultured in growth-restricting medium.

Abstract: Culture conditions which maintain hepatocytes in their in vivo state are not known. This hampers the study of liver gene expression and of direct responses of liver genes to hormonal stimulation. We argued that hepatocytes that were unable to divide might retain in vivo characteristics. We therefore plated mouse (BALB/ c) hepatocytes on plastic dishes in medium lacking arginine and measured the levels and transcription rates of six tissue-specific mRNAs over a period of days. Alpha-fetoprotein mRNA began to ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…By analogy with the mechanism of action of other steroid hormones (61), the data suggest that testosterone, through its receptor, is acting on sequences within the 2.2-kb BS6 promoter region to increase transcription. As yet it is not known whether the cis-acting signals responsible for the effects of thyroxine and growth hormone on MUP RNA synthesis in the liver (33,54) are also present.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By analogy with the mechanism of action of other steroid hormones (61), the data suggest that testosterone, through its receptor, is acting on sequences within the 2.2-kb BS6 promoter region to increase transcription. As yet it is not known whether the cis-acting signals responsible for the effects of thyroxine and growth hormone on MUP RNA synthesis in the liver (33,54) are also present.…”
Section: Resultsmentioning
confidence: 99%
“…Probe A, the BamHI-to-BamHI HSV fragment of pTK1 (59) After recovery, these were combined to make a set of markers. Run-on transcription assays were performed as described (54). The plasmid target sequences were pTK1, MUP11 (10), and LVB6 (54).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several previous studies have shown that variations in apoAl gene expression in response to developmental (17,22), differentiation (2,32), and hormonal (1, 34) factors and various pharmacologic (33) and toxic (21) transactivates the basal promoter, binding of ARP-1 does not; it is important to emphasize that RXRa/ARP-1 heterodimers also bind to site A with an affinity (Kd = 0.6 nM) approximately 10 times greater than the affinity of either ARP-1 (Kd = 5.2 nM) or RXRa (Kd = 8.8 nM) alone. Furthermore, under cotransfection conditions favoring a greater intracellular concentration of RXRa/ARP-1 heterodimers over the concentration of ARP-1, the expression of the site A containing basal apoAI promoter in response to RXRoa and RA is significantly reduced compared with its expression in the absence of ARP-1.…”
Section: Discussionmentioning
confidence: 99%
“…The group 1 liver MUPs are secreted into the plasma and when excreted make up most if not all of the urinary MUP. The expression of the group 1 genes is strongly dependent on testosterone, thyroxine, and growth hormone (9,17,23,29,30). The dependency on testosterone leads to sexual dimorphism in Mup expression, and female expression can be induced to male levels by testosterone induction (9).…”
mentioning
confidence: 99%